2019
DOI: 10.1017/s0031182018002159
|View full text |Cite
|
Sign up to set email alerts
|

Parasite diversity associated with African penguins (Spheniscus demersus) and the effect of host and environmental factors

Abstract: The African penguin (Spheniscus demersus) is a critically endangered species endemic to southern Africa. Limited information is available on the parasite diversity associated with the species in natural settings. This study explores the diversity and incidence of parasites associated with African penguins and their nests, and records the effect of host and environmental factors on parasite infestation. Ecto-, haemo- and helminth parasites were recorded from 210 adult birds, 583 chicks and 628 nests across five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 67 publications
(92 reference statements)
1
7
0
Order By: Relevance
“…The higher soil temperature and moisture in active nests than non-active nests may be attributed to the heat and moisture radiation from the host's body and faeces (Rothschild and Clay 1952;Marshall 1981). Active nests also harboured higher flea infestations, which is consistent with the intimate relationship between fleas and hosts (Bitam et al 2010;Espinaze et al 2019b). Flea larvae indirectly benefit from nest occupancy as their diet includes host organic refuse (Rothschild and Clay 1952).…”
Section: Discussionsupporting
confidence: 76%
“…The higher soil temperature and moisture in active nests than non-active nests may be attributed to the heat and moisture radiation from the host's body and faeces (Rothschild and Clay 1952;Marshall 1981). Active nests also harboured higher flea infestations, which is consistent with the intimate relationship between fleas and hosts (Bitam et al 2010;Espinaze et al 2019b). Flea larvae indirectly benefit from nest occupancy as their diet includes host organic refuse (Rothschild and Clay 1952).…”
Section: Discussionsupporting
confidence: 76%
“…The prevalence of external parasites in this study was remarkably higher than that reported for wild African penguins at the Western Cape (Table 3). In part, this may be related to the fact that our sample largely corresponded to penguins from mainland colonies, which are known to have a higher prevalence of fleas, ticks and Babesia / Plasmodium than island colonies (Espinaze et al ., 2019). Perhaps more significantly, however, the generally higher prevalence of parasites seen in this study might be related to the fact that our sample consisted of individuals that were brought for rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Blood parasites were remarkably common in African penguins examined in this study, with Babesia being the most frequent (46% prevalence on admission, 72% infection ratio), whereas Borrelia was recorded only sporadically (1% prevalence on admission, 3% infection ratio) and Plasmodium was only recorded once. Although these parasites have long been known to infect wild African penguins (Coles, 1941; Fantham and Porter, 1944), their prevalence in this study was markedly higher than in apparently wild healthy adult African penguins sampled in previous studies (Parsons et al ., 2016; Espinaze et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations